(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Women are most powerful consumers in the world as theycontrol almost 80 percent of the household spending. And no longer can thewomen’s spending powers and influence be neglected. The role of women in thesociety and their effects has changed. Most of the marketers know that ‘womenare different’, but we actually need a deep rooted understanding of how and whythey are different. The multiple and often conflicting, roles of women todaypose significant challenges for marketers and researchers. This paper discussesactual and anticipated changes in women’s consumer behavior on the basis ofissues raised by studies of women’s roles in non-marketing disciplines.Implications for research, marketing strategy, and public policy are discussed.Change brought about by the continuing evolution in women’s roles haveaffected, and will continue to affect, all aspects of our society. The purposeof this paper is to analyze the actual and anticipated effects of thesechanging roles on women’s consumer behavior. The issues treated herein arethose raised by the other five participants in this session. Underlying themulti-disciplinary approach taken in this session is a strong belief that wecan better understand and anticipate the effects of women’s changing roles onconsumer behavior if we make use of knowledge available in the behavioralsciences and economics. As an organizing framework, I will first treat issuesdirectly observable in current demographic trends and then treat someinterpersonal issues.